KARAKTER FISIK KULIT DOMBA SAMAK KOMBINASI DENGAN BAHAN PENYAMAK ALUMUNIUM-MIMOSA - Swatika Juhana; Tutik Maryati; Wahyu Fajar Winata (Politeknik ATK Yogyakarta, 2020)
Sheep skin tanning has been carried out using a combination tanning material, namely 4% Aluminum and 6% Mimosa. Raw materials in the form of raw sheep skin weighing 2 kg. BHO, tanning, and post tanning processes are carried out to produce crust skin. The physical test characteristics are 0.7 mm thickness, 6 mm softness, 27.8 N/mm2 transverse tensile strength, 17.8 N/mm2 longitudinal tensile strength, 48.5 % transverse elongation, 45.8 % longitudinal elongation, 19.1 N/mm2 transverse tear strength, 18.9 N/mm2 longitudinal tear strength, and shrinkage temperature (Ts) 89oC. The physical test results were compared with the SNI 4593-2011 standard for sheep leather jackets. The results meet the SNI for sheep leather jackets.